Ansiedad y su incidencia en las relaciones interpersonales y de un adoleste de 17 años de edad de la ciudad de Babahoyo - Dominguez Icaza, Elvis Adrian (2022)
The purpose of this case study is to determine the incidence of anxiety in the interpersonal relationships of a 17-year-old adolescent from the city of Babahoyo, for which an investigation is used, which will help us to solve the different variables, as son; anxiety and interpersonal relationships, in which the study is going to deepen, also taking into account that with the help of different psychological tools, such as clinical history, psychometric tests and techniques of the cognitive behavioral approach, this being the key to be able to reach a presumptive diagnosis with the patient. For the intervention, a therapeutic scheme of cognitive behavioral model is elaborated, in order to restructure the patient's impaired cognition, reintegrate him into his social life, reduce the patient's psychic and physical manifestations.